Efficient use of energy in anoxia‐tolerant plants with focus on germinating rice seedlings. Issue 1 (4th December 2014) - Atwell, Brian J.; Greenway, Hank; Colmer, Timothy D.
Summary: Anoxia tolerance in plants is distinguished by direction of the sparse supply of energy to processes crucial to cell maintenance and sometimes to growth, as in rice seedlings. In anoxic rice coleoptiles energy is used to synthesise proteins, take up K +, synthesise cell walls and lipids, and in cell maintenance. Maintenance of electrochemical H + gradients across the tonoplast and plasma membrane is crucial for solute compartmentation and thus survival. These gradients sustain some H + ‐solute cotransport and regulate cytoplasmic pH. Pyrophosphate (PPi ), the alternative energy donor to ATP, allows direction of energy to the vacuolar H + ‐PPi ase, sustaining H + gradients across the tonoplast. When energy production is critically low, operation of a biochemical pHstat allows H + ‐solute cotransport across plasma membranes to continue for at least for 18 h. In active (e.g. growing) cells, PPi produced during substantial polymer synthesis allows conversion of PPi to ATP by PPi ‐phosphofructokinase (PFK). In quiescent cells with little polymer synthesis and associated PPi formation, the PPi required by the vacuolar H + ‐PPi ase and UDPG pyrophosphorylase involved in sucrose mobilisation via sucrose synthase might be produced by conversion of ATP to PPi through reversible glycolytic enzymes, presumably pyruvate orthophosphate dikinase. These hypotheses need testing with species characterised by contrasting anoxia tolerance. Contents Summary 36 I. Introduction 36 II. PPi ‐dependent enzymes as a key adaptation to an energy crisis, enabling survival and growth in anoxia 37 III. Mechanisms of survival during an energy crisis: that is, plant quiescence during anoxia with no growth and acclimated cells in anoxia 44 IV. Energy expenditure during growth under anoxia 49 V. Conclusions on mechanisms of anoxia tolerance 53 Acknowledgements 54 References 55